The Relationship between Leadership Style and Work Motivation of Nurse in Hospital - Ryandini, Tiara Putri; Nurhadi, Mokhamad (Fundamental and Management Nursing Journal, 2020)
Introduction: One that supports the work motivation of nurses is a democratic leadership style, where the democratic leadership style itself is the participation of subordinates in deliberative decision making. A nurse who works in an inpatient unit must have high work motivation inbut in fact many nurses are not enthusiastic in carrying out their duties because the leadership style applied by the head of the room is not suitable. The purpose of this study was to determine the relationship between the leadership style of the head of the room on the work motivation of nurses in the inpatient room of dr. R. Koesma Tuban.Methods: The study design was cross sectional. The population in this study were all nurses in the inpatient room of dr. R. Koesma Tuban according to the inclusion criteria as many as 47 respondents with a large number of research samples 42 respondents, then using the cluster sampling technique as a method of sampling. The instrument uses a questionnaire. The data were analyzed using the Contingency Coefficient.Results: Based on the research results, it was found that almost all of the nurses considered that the leadership style of the head of the room owned was democratic, and most of the nurses had high motivation. The results of the contingency coefficient were obtained, the leadership style variable (p <0.05) had a moderate correlation with the work motivation of nurses (r = 0.542), and the direction of the positive correlation, which meant that the more democratic the leadership style of the head of the room, the higher the nurse's work motivation.Conclusion: There is a relationship between the leadership style of the head of the room with the work motivation of nurses in the inpatient room of dr. R. Koesma Tuban. So it is expected that the head of the room can apply a democratic leadership style so that it can increase the motivation of nurses who are still low. order to be able to carry out nursing care properly,